Oral tradition as history - Vansina, Jan (Wisconsin : The University of Wisconsin Press, 1985)
A comprehensive study of the importance of oral tradition of various ancient societies to the work and research of students and scholars of history, anthropology, folklore, and ethno-history
Oral tradition as process -- Performance, tradition, and text -- Getting the message -- The message is a social product -- The message expresses culture -- Tradition as information remembered -- Oral tradition assessed
Includes bibliographical references (pages 229-245) and index
Keywords: Oral tradition; History -- Methodology; Oral tradition -- Africa; Africa -- History -- Methodology